Phytotherapy for Cachexia: Where Do We Stand? - Kuchta, Kenny; Cameron, Silke (Frontiers in Pharmacology, 2020)
Background In contrast to Western medicine which currently offers no approved pharmacotherapy options for cachexia, in Japan multi-component extracts of medicinal plants are used with coverage by the national health insurance. This so called “Kampo” medicine is an example of the modern concept of multi-component/multi-target therapy. For the three traditional preparations Hochuekkito (補中益気湯), Juzentaihoto (十全大補湯), and Rikkunshito (六君子湯), a multitude of clinical research data relating to cachexia has been published. These preparations are also referred to as “Hozai” (補剤). A similar concept is found in Russian herbal medicine, where the term “Adaptogen” was coined for pharmacologically active substances which enhance adaptive stress repose. Methods Scientific literature—including original Japanese articles—was reviewed regarding the effects of these herbal preparations on cachexia. Cachexia is a complex set of symptoms including muscle atrophy with loss of weight, fatigue, and weakness. Results In a 1985 study by Kuroda et al., Hochuekkito showed efficacy in involuntary weight loss and fatigue in 63% of 162 patients with genitourinary cancer. For cancer-related fatigue, a significant improvement was reported within 2 weeks by Jeong et al. in 2010. In patients with chronic fatigue syndrome, Hochuekkito showed an overall improvement with 8–12 weeks of therapy in a 1997 study by Kuratsune et al. In a 2005 randomized placebo-controlled trial by Satoh et al. on 13 geriatric Q1 patients in a 16-week treatment protocol, Hochuekkito showed significant improvement of general health, physical functioning and the Profile of Mood States (POMS). In 71 geriatric COPD patients in a 2009 placebo-controlled randomized study, Tatsumi et al. found a significant body weight increase and a CRP, TNF-α, IL-6 decrease over 6 months of therapy. For Juzentaihoto in 48 hepatocellular carcinoma patients, Tsuchiya et al. 2008 documented a significantly longer recurrence-free survival (49 vs. 24 months) as compared to the control group (p=0.023). For the much simpler Rikkunshito prescription, a 2011 retrospective study by Fujitsuka et al. on 39 Stage III/IV pancreatic cancer patients treated with Gemcitabine (n=33) or Gemcitabine/Rikkunshito (n=6) showed a significantly prolonged median survival with 224 vs. 378.5 days (p < 0.05). In a 2011 open-label clinical study by Utumi et al. on geriatric cachexia in 6 dementia patients, treatment with Rikkunshito for 4 weeks resulted in a significant body weight increase. In all the above studies, the standardized dosage of 3x2.5 g/d extract granules for most Japanese health insurance-covered Kampo extract-preparations was applied. Conclusion As there is currently no accepted pharmacotherapy option for cachexia available in the West, a transfer of these East Asian gold standard prescriptions into the European market would be desirable. We were further able to demonstrate that the mTOR, interleucin, and melatonin pathways are modified by herbal compounds which thus counteract cachexia. More research in this field is urgently needed in order to provide new, effective treatments for cachexia patients.